The composing and combining between Al-kadi Abd al-Jabar and Abd-alkaher Aljurjani.(An inter-textual reading) (Journal of Hama University, 2021)
The research examines some relations between two heritage-cultural texts has been referenced to their interactions ; the verbal text by Al- kadi Abd al-Jabar and the critical rhetorical text by Abd-alkaher Aljurjani via utilizing the intertextuality strategy in interpreting and reading the text through composing and combining concepts. Thus, the research depends on the subsequent text (Aljurjani), inquiring the textual-entangled categories and the types of relations to the hidden text, in addition to the functioning and transforming methods. Indeed, the study importance comes from the epistemological approach which it relies upon, because intertextuality in reading the critical text has been neglected in the Arabic studies that rather focus on creative texts .To conclude, the sample of the research reveals the agency of the intertextuality at interpreting a critical text and how pivotal to be focused on as a reading strategy reinforcing the essential themes of the critical text, such as the dialogism, which reads the implications of the text to reveal its structural strategies and relations to subsequent and modern texts.